(untitled) (Economics and region, 2020)
The article examines the essence, types, meaning and composition of enterprise resources, conducts a theoretical study of the classification of resources and their significance for the enterprise. Such concepts as "enterprise resources" and the main indicators that characterize it are revealed. The study of the views of scientists has shown that the concept of "resources" is quite controversial. The study of literature has shown that there are many different definitions and types of resources, depending on the type of activity of the enterprise, sources of formation or directions of use. The main indicators that characterize the company’s resources are described and reserves and directions for their effective use are identified.